How long does it take to know a species? Redescription, vocalization, and chigger mites infestation pattern in the centenary Brachycephalus garbeanus (Anura: Brachycephalidae) - Folly, Manuella; Woitovicz-Cardoso, Manoela; Canedo, Clarissa; Nogueira-Costa, Paulo; Pombal, José P. Jr. (Zootaxa, 2021)
Although we celebrate the centennial of Brachycephalus garbeanus’ discovery, little progress has been done on understanding this species’ biology apart from a few morphological and ecological studies, which includes its redescription based on three specimens from the type-series, microhabitat use, sexual dimorphism in body size, and feeding habits. This species is endemic to the Serra dos Órgãos Mountain range, in the state of Rio de Janeiro, southeastern Brazil. Here we redescribe B. garbeanus based on a wide sampling, including its advertisement and aggressive calls, and also the chigger mites infestation pattern. The advertisement call is longer than 25.8 s with pulsed notes series emitted at an average rate of 2.3 notes/s and 14.1 pulses/s; long inter-note interval with 320 ms; notes with distinctly short pulses (1 to 16 ms); low dominant frequency for this genus (3.0-5.4 kHz) and presence of four harmonics. This species is often parasitized by chigger mites of Hannemania, with a prevalence of infection of 67%, mainly affecting the ventral body surface. Females had a higher prevalence of parasites than males and there was no correlation found between the size of specimens and the number of parasites. Our study, provides an important and overdue taxonomical contribution, including a large amount of novel information for B. garbeanus.